Clinical Profile of COVID-19 Older Patients Hospitalized in Immanuel Teaching Hospital Bandung - Vera, Vera; Suprana, Yossie Guventri Eka (UI Scholars Hub, 2022)
Introduction. It was reported that 11.2% out of the 78,572 confirmed cases of COVID-19 in Indonesia was foundinolder people with a high mortality rate. There is no available data regarding functional and frailty status of these COVID-19 older patients. This study aimed to describe clinical profile of older COVID-19 patients in terms of geriatric aspect, in order to design better hospital policy for older patients in the COVID-19 isolation ward.Methods. This was a retrospective cohort study of confirmed COVID-19 patients aged >60 years which were admitted to Immanuel Teaching Hospital Bandung during the period of October 2020 - January 2021. Clinical characteristic data, frailty status, mode of oxygen therapy, functional status (activity of daily living – ADL) during and after hospitalization, as well as patient hospitalization outcomes were recorded from the medical record.Results. There were 100 COVID-19 older patients, more than half were aged 60-70 years, most with not frail status. This study found that 74% of older patients had decreased ADL scores, once they got infected with COVID-19. We also found that 43% of COVID-19 older patients died during hospitalization, dominated by frail patients. Among COVID-19 older survivor, 55%had increased ADL score when discharged. A month later, only 25%patients had better ADL scores.Conclusion. Typical symptoms of COVID-19 are not always found in older patients. Apart from its deadly consequence and prolonged hospitalization, the impact of COVID-19 on older patients is decreased functional status, so special management policy for older COVID-19 patients should be considered.